Konsep Tazkiyah An-Nufūs Perspektif Ibnu Miskawaih dan Relevansinya dengan Pendidikan Karakter: Studi Kitab Tahżīb al-Akhlāk - Nuning Kartikasari; Fajar Rachmadhani (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2026)
Education plays an important role in shaping people’s personality and characters. This is in accordance with the objectives of national education as stated in Law No. 20 of 2003, Article 3 concerning the National Education System, that national education serves to develop abilities and shape the character and civilization of a dignified nation to enlighten the nation's life. National education aims to develop the potential of students to become human beings believing and fearing the Almighty God, have noble characters, are healthy, knowledgeable, capable, creative, and independent, as well as becoming democratic and responsible citizens. This study aims to analyze and describe the concept of tazkiyah an-nufūs from Ibn Miskawayh's perspective and the relevance of the concept of tazkiyah an-nufūs from Ibn Miskawayh's perspective on character education. The research method employed qualitative with descriptive analysis, where the data sources were obtained from primary data, namely the book of Tahżīb al-Akhlāk wa Taṭhīr al-A'rāq and secondary data sourced from journals, articles, and theses related to this research topic. Then, the analysis technique used applied three steps of data reduction, data reduction, and conclusion drawing. The results of this study suggest that the concept of tazkiyah an-nufūs from Ibn Miskawayh consists of four concepts: Hikmah (wisdom), ̀'Iffah (self-control), Syaja ̀ah (courage), and ̀Adalah (justice). Then, between the concept of tazkiyah an-nufūs from Ibn Miskawayh and character education in Indonesia, there is a relevance between the four concepts above and the eighteen-character values instilled in all schools in Indonesia.